2014
DOI: 10.1371/journal.pone.0091689
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Obesity among Panamanian Adults. 1982–2010

Abstract: BackgroundIn Central America, there has been a marked increase in obesity in the last 30 years. Over this time frame, in Panama, there have been lifestyle changes associated with economic development and urbanization that may have facilitated increases in body weight. The aim of the study is to describe the change in the prevalence of obesity in the country since 1982 and to analyze the association of obesity with gender, place of residence and socioeconomic factors.MethodsWe analyzed three nationally represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
2
15
0
6
Order By: Relevance
“…The Panamanian population has experienced a marked increase in obesity and this is particularly evident among females. 41 Other factors, such as reproductive behavior and lifestyle modifications, could also be contributing factors to the increase incidence in breast cancer in Panama. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The Panamanian population has experienced a marked increase in obesity and this is particularly evident among females. 41 Other factors, such as reproductive behavior and lifestyle modifications, could also be contributing factors to the increase incidence in breast cancer in Panama. 38 …”
Section: Discussionmentioning
confidence: 99%
“…This increase could possibly be influencing the elevation of mortality from stroke and IHD noted in this younger age groups. Moreover, a Panamanian study reported that the prevalence of obesity has been increasing in both sexes, particularly in women 29. The prevalence of obesity in the PREFREC study was 30.9% in women and 18.3% in men.…”
Section: Discussionmentioning
confidence: 92%
“…La situación se agrava al inferir estas cifras a la población, dado que en ese período, el crecimiento poblacional se duplicó. Una similar tendencia se reporta en países como en Colombia donde la prevalencia de obesidad pasó de 13,9% a 16,4%, en el período comprendido entre el 2005 al 2010 13 ; lo mismo sucedió en Panamá donde fue de 3,8% en los varones y de 7,6% en las mujeres, pasando a 16,9% y 23,8% entre los años 1982 a 2008 14 .…”
Section: Discussionunclassified
“…Respecto a la presencia del sobrepeso y obesidad en relación a los grupos de edad, se observa que la prevalencia se ha incrementado y que es a partir de los 60 años donde empieza a disminuir; esto también ha sido reportado en población panameña 14 . En este grupo etareo se presentan riesgos que están asociados a la obesidad junto a la pérdida de masa corporal, conocido como obesidad sarcopénica.…”
Section: Discussionunclassified